2021
DOI: 10.1016/j.jbc.2021.101274
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic degradation of IRF3 induced by the small-molecule auranofin inhibits its transcriptional and proapoptotic activities

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…We have recently conducted a high-throughput screen to isolate novel small molecules that regulate viral apoptosis [ 54 ]. The screen also isolated auranofin, which inhibited the cellular IFN response [ 55 ]. We showed that auranofin activates the cellular autophagy pathway, degrading the IRF3 protein to block the IFN response ( Figure 4 ).…”
Section: Autophagy and The Interferon Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently conducted a high-throughput screen to isolate novel small molecules that regulate viral apoptosis [ 54 ]. The screen also isolated auranofin, which inhibited the cellular IFN response [ 55 ]. We showed that auranofin activates the cellular autophagy pathway, degrading the IRF3 protein to block the IFN response ( Figure 4 ).…”
Section: Autophagy and The Interferon Systemmentioning
confidence: 99%
“…Numerous reports suggest that SARS-CoV-2 entry may depend on the autophagy pathway; therefore, these autophagy inhibitors may be used to counteract the replication of the CoV-2 virus. We have shown that auranofin, an anti-rheumatic compound, induces autophagy to degrade IRF3 [ 55 ]. Auranofin has also been shown to inhibit SARS-CoV-2 replication [ 94 ]; whether auranofin degrades a viral protein or a pro-viral host protein in this context will require future evaluation.…”
Section: Therapeutic Application Of Autophagy In Virus Infectionmentioning
confidence: 99%
“…The optimal physiological function of IRF3 in innate antiviral defense depends on its transcriptional and nontranscriptional (nt) activities ( 24 , 35 , 44 , 45 , 64 , 71 ). In addition to the widely studied role of IRF3 as a transcription factor, we demonstrated a proapoptotic function for nt-IRF3, RIPA, which protects the host from viral pathogenesis and contributes to fatty liver diseases ( 35 , 41 , 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Auranofin inhibited fatty acid-induced hepatocyte apoptosis in an in vitro model by inducing cellular autophagy and thereby degrading IRF3. 5 Auranofin is also known as a pan-inhibitor of thioredoxin reductase (TrxR). 6 By inhibiting TrxR, auranofin induced apoptosis in HCC cells and inhibited tumor growth, together with improved resistance to sorafenib.…”
Section: Dear Editormentioning
confidence: 99%
“…The interferon regulatory factor 3 (IRF3) signaling pathway promotes hepatocyte inflammation and apoptosis in NAFLD [ 4 ]. Auranofin inhibited fatty acid-induced hepatocyte apoptosis in an in vitro model by inducing cellular autophagy and thereby degrading IRF3 [ 5 ].…”
mentioning
confidence: 99%